Italian Radicals in Canada: A Note on Sources in Italy - Iacovetta, Franca; Ventresca, Robert (Labour / Le Travail, 1996)
Discusses and provides examples of documentation of Italian radicals in Canada at the Casellario Politico Centrale (Rome), the files of which were extensive during the Fascist dictatorship in Italy (1922-43) since the regime wanted to identify and monitor its opponents. Argues that these materials may be used to write the history of the Italian left/anti-Fascism in Canada as well as contributing to studies of Canadian labour/immigration history and the international anti-fascist movement.
Keywords: Canada; EMIGRATION & immigration; FILES (Records); History; IACOVETTA, Franca; LABOUR/LE Travail (Book); Labor; RADICALS; VENTRESCA, Robert

Women's History, Gender History and Debating Dichotomies - Iacovetta, Franca; Kealey, Linda (Left History: An Interdisciplinary Journal of Historical Inquiry and Debate, 1996)
Joan Sangster's "Beyond Dichotomies" (left history, 3.1, Spring/Summer 1995) is a polemic on the relationship between women's history and gender history. As such, it tends to bring out issues and highlight debates but, at the same time, it sometimes inevitably simplifies and potentially misrepresents in order to address important points. As friends and colleagues, we would like to take issue with some of the assertions and suggestions made in Sangster's piece. We think it is important to debate these issues and we hope to make a contribution. Such issues are central in feminist historical debates internationally and, while individuals who write Canadian women's history and gender history have clearly borrowed from the intemational literature, there has been no sustained Canadian "debate," at least not in print. --Introduction